Uma análise crítica do termo organizações intensivas em conhecimento - Nadai, Fernanda C. de (Revista Gestão da Produção Operações e Sistemas, 2006)
The intense competition among the markets requires from the companies ability to develop and manage efficiently their financial, structural or personnel resources. In the literature, there is the prevalence of approaches considering the capital as the main resource to be managed. However, in the economy based on information and intensive service, efficiency, flexibility, innovation and qualified personnel become essential aspects so that the organizations maintain competitive. Facing this reality, knowledge must be considered a valuable and strategic resource in the establishment of a sustainable competitive advantage in the organizations. However, regarding the intensive organizations in knowledge, it becomes an essential feature. The proposal of this paper is to incite a discussion on what really determines that a company be intensive in knowledge, a term used to classify this type of organization in some literature papers in order to classify this type of organization. Some organizational characteristics which could determine this classification are presented here: performed activities, personnel, operating market, products, services and management practices. Based on such characteristics, it is possible to define an intensive organization in knowledge. Keywords: Knowledge; Strategic resource; Intensive organization in knowledge.